ON THE PRESENCE OF PYRAMIODONTHERIUM (MAMMALIA, XENARTHRA, MEGATHERIIDAE) IN THE LATE MIOCENE OF NORTHEASTERN ARGENTINA AND ITS BIOGEOGRAPHICAL IMPLICATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
The biochron of the subfamily Megatheriinae, large to very large terrestrial sloths typified by Megatherium Cuvier, in Argentina extends from the middle Miocene of Patagonia to the late Pleistocene-early Holocene. Megatheriines reached their highest diversity in the lower levels (="conglomerado osífero", late Miocene) of the Ituzaingó Formation in Entre Ríos Province, northeastern Argentina. Among the four megatheriines that occur in this unit, the genera Promegatherium Ameghino, Eomegatherium Kraglievich and Pliomegatherium Kraglievich represent relatively small to medium-sized taxa. Here we describe new material assigned to Pyramiodontherium, the largest of the four genera from the same bed and comparable in size to some Quaternary species of Megatherium. Three valid species of Pyramiodontherium have been recognized, all distributed mainly in northwestern Argentina, from the late Miocene in Catamarca Province (and probably also in Tucumán Province), and the late Pliocene in La Rioja Province. The presence of this genus in northeastern Argentina extends its known paleobiogeographical distribution.
Keywords: Argentina; Biogeography; Late Miocene; Megatheriinae; Pyramiodontherium; Systematics